Modeling population dynamics Anoda cristata in a glyphosate-resistant soybean crop under different management systems - Puricelli, E.=700 1 Vitta, J.I.; Sabbatini, M.R.; Orioli, G.
(Es, En)
Ilus., 27 ref.
Keywords: MALVACEAE; MALEZAS; ESCARDA; CONTROL DE PLAGAS; CONTROL QUIMICO; GLIFOSATO; DOSIS DE APLICACION; BANCO DE GENES; SOJA; DINAMICA DE LA POBLACION; ARGENTINA; ANODA CRISTATA; AGRISCIENTIA